(untitled) (Research, Society and Development, 2021)
This study sought to verify the action of red propolis as an edible coating in the conservation of the apple of the cultivar “Fuji”, using temperatures of 7 ° C (refrigerated) and 30 ° (ambient) and in the concentrations of propolis at 3% and 5%, for the research, this fruit was used for its nutritional value, rich pectin, tannin and flavonoids, which are phytonutrients, which act as antioxidants and prevent various diseases. The filmogenic solution applied was red propolis extract, which has substances that delay the ripening of the cultivar, thus contributing to the increase of its useful life. The samples were immersed in the concentrations, then placed in their proper environments, from where they were taken every 5 days, for 30 days, microbiological analyzes were carried out, which confirmed the absence of Salmonela ssp and Staphylococcus spp, and the delay of the development of filamentous fungi, coliforms 35 ° and coliforms 45 ° until the 15th day for the concentration at 3%, and 25 days for the 5%, confirming the efficiency of the coating against the development of Microorganism, In relation to physical-chemical , the samples showed an interaction in the ratio, contributing to the ripeness of the fruit.